2023
DOI: 10.1039/d3ce00091e
|View full text |Cite
|
Sign up to set email alerts
|

Insight into polymorphism and dynamics of aripiprazole

Abstract: Phase sequence and molecular dynamics (molecular relaxation processes) of aripiprazole were studied by X-ray diffraction (XRD), differential scanning calorimetry (DSC), polarizing optical microscopy (POM), and broadband dielectric spectroscopy (BDS). Polymorphism...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Our results obtained for the quenched APZ are in good agreement with DSC data published for this API by Knapik-Kowalczuk et al, 53 which showed similar values of T g (306 K), T c (363 K), and T m (∼406 and ∼412 K). In addition, nearly the same melting temperatures (T m = 405.7 and 411.4 K, assigned, respectively, to the IV and III polymorphs of APZ) were determined from calorimetric measurements carried out by Osiecka-Drewniak et al 16 DSC curves collected for APZ infiltrated into three types of templates differ from those measured for the quenched (bulk) sample since they revealed the presence of the two well-visible glass transition events located below and above T g of the bulk API (see Figure 1(c,d)). According to the "two-layer"( or "core-shell") model, 54,55 this phenomenon, known as a "double glass transition" (DGT), reflects the presence of two groups of molecules with different mobility: (i) "interfacial", interacting directly with the inner surface of the pore wall and characterized by a higher T g (so-called T g , interfacial ), as well as (ii) "core", located in the middle of nanochannels, which are characterized by bulk-like mobility and lower T g (assigned as T g,core ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results obtained for the quenched APZ are in good agreement with DSC data published for this API by Knapik-Kowalczuk et al, 53 which showed similar values of T g (306 K), T c (363 K), and T m (∼406 and ∼412 K). In addition, nearly the same melting temperatures (T m = 405.7 and 411.4 K, assigned, respectively, to the IV and III polymorphs of APZ) were determined from calorimetric measurements carried out by Osiecka-Drewniak et al 16 DSC curves collected for APZ infiltrated into three types of templates differ from those measured for the quenched (bulk) sample since they revealed the presence of the two well-visible glass transition events located below and above T g of the bulk API (see Figure 1(c,d)). According to the "two-layer"( or "core-shell") model, 54,55 this phenomenon, known as a "double glass transition" (DGT), reflects the presence of two groups of molecules with different mobility: (i) "interfacial", interacting directly with the inner surface of the pore wall and characterized by a higher T g (so-called T g , interfacial ), as well as (ii) "core", located in the middle of nanochannels, which are characterized by bulk-like mobility and lower T g (assigned as T g,core ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our results obtained for the quenched APZ are in good agreement with DSC data published for this API by Knapik-Kowalczuk et al, 53 which showed similar values of T g (306 K), T c (363 K), and T m (∼406 and ∼412 K). In addition, nearly the same melting temperatures ( T m = 405.7 and 411.4 K, assigned, respectively, to the IV and III polymorphs of APZ) were determined from calorimetric measurements carried out by Osiecka-Drewniak et al 16 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations